Algebraic approach to the analysis of legal documents - Letychevskyi, O.O.; Peschanenko, V.S.; Poltorackiy, M.Yu. (Проблеми програмування, 2022)
In this study, problems regarding the analysis of law articles and their conformance to legal documents are considered. The algebraic approach is used for the formal verification of legal texts that is presented as specification of behavior algebra. Having a formal presentation of legal texts allows for the application of algebraic methods, such as symbolic modeling, automatic proving of statements and algebraic matching. The approach was implemented for Ukrainian-language legal documents to detect inconsistency, incompleteness, and prove conformance. The analysis of legal texts has been implemented for Tax code and examples of inconsistency of some statements were demonstrated in the paper. Another experiment has been performed for checking of conformance of court statements, agreements, licenses, new laws, taxation acts to the articles of law with usage of methods of algebraic matching. The formalization of legal documents, like court verdicts, shall be implemented fully automatically, and the existing database with such documents shall provide the possibility to use big data technologies and machine learning. In this study, we consider the use of the algebraic approach in the analysis of legal requirements and law artifacts within the scope of the Insertion Modeling System (IMS). The subject of this research is the laws created by the legislature and the artifacts of legal activity, such as lawsuit decisions, agreements, licenses, and juridical cases. The problem to be considered is the analysis of legal documents for conformance with the law and the analysis of the law’s articles, checking for inconsistencies, incompleteness, and other interested properties. In this paper, we consider every element of the technology in detail, and we describe the methods and results of the experiments. У даному дослідженні розглядаються проблеми аналізу статей законодавства та їх відповідності правовим документам. Ми пропонуємо використання алгебраїчного підходу для формальної верифікації юридичних текстів, які представляються у вигляді специфікації алгебри поведінки. Наявність формального представлення юридичних текстів дозволяє застосовувати алгебраїчні методи, такі як символічне моделювання, автоматичне доведення тверджень і алгебраїчне зіставлення. Підхід реалізовано для україномовних правових документів для виявлення невідповідності, неповноти та підтвердження відповідності. Було здійснено аналіз законодавчих актів для Податкового кодексу і наведено приклади невідповідності деяких тверджень. Проведено ще один експеримент для перевірки відповідності судових актів, договорів, ліцензій, нових законів, актів про оподаткування статтям законодавства з використанням методів алгебраїчного зіставлення. Формалізація юридичних документів, таких як судові рішення, має здійснюватися повністю автоматично, а існуюча база даних із такими документами має забезпечувати можливість використання технологій big data та машинного навчання. У цьому дослідженні ми розглядаємо використання алгебраїчного підходу в аналізі законодавчих вимог і правових документів у межах системи інсерційного моделювання. Предметом дослідження є створені законодавчою владою закони та юридичні документи, такі як судові рішення, угоди, ліцензії та судові справи. Проблемою, яка розглядається, є аналіз нормативно-правових документів на відповідність закону та аналіз статей закону, перевірка на невідповідності, неповноту та інші властивості. У цій роботі ми детально розглядаємо кожен елемент технології, описуємо методику та результати експериментів.